Hypertensive Disorders of Pregnancy and Cardiovascular Disease Risk Across Races and Ethnicities: A Review - Burger, Renée J.; Delagrange, Hannelore; van Valkengoed, Irene G. M.; de Groot, Christianne J. M.; van den Born, Bert-Jan H.; Gordijn, Sanne J.; Ganzevoort, Wessel (Frontiers in Cardiovascular Medicine, 2022)
Pregnancy is often considered to be a ‘cardiometabolic stress-test’ and pregnancy complications including hypertensive disorders of pregnancy can be the first indicator of increased risk of future cardiovascular disease. Over the last two decades, more evidence on the association between hypertensive disorders of pregnancy and cardiovascular disease has become available. However, despite the importance of addressing existing racial and ethnic differences in the incidence of cardiovascular disease, most research on the role of hypertensive disorders of pregnancy is conducted in white majority populations. The fragmented knowledge prohibits evidence-based targeted prevention and intervention strategies in multi-ethnic populations and maintains the gap in health outcomes. In this review, we present an overview of the evidence on racial and ethnic differences in the occurrence of hypertensive disorders of pregnancy, as well as evidence on the association of hypertensive disorders of pregnancy with cardiovascular risk factors and cardiovascular disease across different non-White populations, aiming to advance equity in medicine.